Dynamic changes in the diversity and function of bacterial community during black tea processing. (November 2022) - Jia, Wen-bao; Zhao, Yi-qiao; Liao, Si-yu; Li, Pin-wu; Zou, Yao; Chen, Sheng-xiang; Chen, Wei; He, Chun-lei; Du, Xiao; Zhu, Ming-zhi; Xu, Wei
Graphical abstract: Highlights: Sphingomonas and Variovorax were dominant genera in the black tea processing. Oxidation of catechins may be influenced by microbial enzymes. Rolling and fermentation are important stages in black tea processing. Bacterial community plays an important role in quality formation of black tea. Abstract: Among all types of tea, black tea is produced in the largest amount worldwide, and its consumption is still increasing. Enzymatic fermentation is considered majorly contribute to quality formation of black tea, and the information about the roles of bacterial community in black tea processing is scarce. This study aimed to analyze the dynamic changes in composition, structure, and function of microbial communities during black tea processing and reveal the roles of bacterial community in black tea processing. Results showed that the genera Sphingomonas and Variovorax were dominant throughout the processing of black tea. Prediction function analysis of bacterial community showed that the mean proportions of glucuronoarabinoxylan endo − 1, 4 − beta − xylanase, aminopeptidase B, phosphoserine phosphatase, homoserine O-acetyltransferase, glycolysis related enzymes, pyruvate dehydrogenase, tricarboxylic acid cycle related enzymes, and glyoxylate bypass were significantly elevated in the rolling and fermentation stages. The contents of amino acids, soluble sugar, theaflavins, thearubigins, and theabrownins increased greatly during the rolling and fermentation processes. Redundancy and Pearson's correlation analyses showed that the relative abundance of bacteria was closely related to the contents of water extract, tea polyphenols, epigallocatechin, epicatechin gallate, catechin gallate, thearubigins, theaflavins, and theabrownins. Overall, the findings provided new insights into the variation of bacterial community during black tea processing and improved our understanding of the core functional bacteria involved in black tea processing.